Analysis of the Indonesian Speakers of English Employ the Indonesian Language Syntactically - Nuraziza Aliah; Nurasia Natsir; Khaeriyah Khaeriyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
There is a phenomenon where Indonesians speak English with syntactical interference from Indonesians. This study aims to describe the most common syntactical interference made by the elite group in Indonesia when speaking English. This research also aims to reveal the factors that cause the elite group of Indonesia to use those types of syntactical interference when speaking English. The researcher collected primary data by interviewing and recording 33 respondents from the elite group of Indonesia. The analysis was carried out using quantitative and qualitative descriptive methods. The results show the elite group in Indonesia makes several types of syntactical errors, including omissions, additions, malformations, and disordering. This is due to a lack of awareness in the attempt to translate the original structure of Indonesian into English.